Antiplasmodial activity of Ethanolic extract of Cassia spectabilis DC leaf and its inhibition effect in Heme detoxification - Wiwied Ekasari; Dewi Resty Basuki; Heny Arwati; Tutik Sri Wahyuni (BMC, 2021)
Abstract Background In previous studies, Cassia spectabilis DC leaf has shown a good antiplasmodial activity. Therefore, this study is a follow-up study of the extract of leaf of C. spectabilis DC on its in vitro and in vivo antiplasmodial activity and mechanism as an antimalarial. Methods The extract was fractionated, sub-fractionated and isolated to obtain the purified compound. In vitro antiplasmodial activity test against Plasmodium falciparum to find out the active compound. In vivo test against P. berghei ANKA-infected mice was conducted to determine prophylactic activity and antiplasmodial activity either alone or in combination with artesunate. The inhibition of heme detoxification test as one of the antimalarial mechanisms was carried out using the Basilico method. Results The results showed that active antimalarial compound isolated from C. spectabilis DC leaf had a structural pattern that was identical to (−)-7-hydroxycassine. Prophylactic test of 90% ethanolic extract of C. spectabilis DC leaf alone against P. berghei ANKA-infected mice obtained the highest percentage inhibition was 68.61%, while positive control (doxycycline 13 mg/kg) was 73.54%. In combination with artesunate, 150 mg/kg three times a day of C. spectabilis DC (D0-D2) + artesunate (D2) was better than the standard combination of amodiaquine + artesunate where the inhibition percentages were 99.18 and 92.88%, respectively. The IC50 of the extract for the inhibitory activity of heme detoxification was 0.375 mg/ml which was better than chloroquine diphosphate (0.682 mg/ml). Conclusion C. spectabilis DC leaf possessed potent antiplasmodial activity and may offer a potential agent for effective and affordable antimalarial phytomedicine.